2016
DOI: 10.1136/bmj.i5599
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ischaemic conditioning on major clinical outcomes in people undergoing invasive procedures: systematic review and meta-analysis

Abstract: Objective To summarise the benefits and harms of ischaemic conditioning on major clinical outcomes in various settings.Design Systematic review and meta-analysis.Data sources Medline, Embase, Cochrane databases, and International Clinical Trials Registry platform from inception through October 2015.Study selection All randomised controlled comparisons of the effect of ischaemic conditioning on clinical outcomes were included.Data extraction Two authors independently extracted data from individual reports. Repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…It is possible that RIPre is more effective than RIPost. This may be supported by the observation that in a large meta‐analysis, ischemic preconditioning tends to have a more favorable effect on reducing myocardial injury compared to ischemic postconditioning . We expected at least a modest effect with RIPost in our study, which included a higher‐risk population, such as patients presenting with unstable angina in contrast to the CRISP study, which included only elective patients.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…It is possible that RIPre is more effective than RIPost. This may be supported by the observation that in a large meta‐analysis, ischemic preconditioning tends to have a more favorable effect on reducing myocardial injury compared to ischemic postconditioning . We expected at least a modest effect with RIPost in our study, which included a higher‐risk population, such as patients presenting with unstable angina in contrast to the CRISP study, which included only elective patients.…”
Section: Discussionmentioning
confidence: 68%
“…The beneficial effect of RIPre in the setting of PCI was also confirmed in meta‐analyses . However, in a large meta‐analysis that included application of ischemic conditioning in multiple settings, overall ischemic conditioning had no effect on major cardiovascular outcomes, and so far we have not witnessed the translation of ischemic conditioning into clinical practice …”
Section: Introductionmentioning
confidence: 84%
“…Though several meta-analyses found a reduction of AKI [278, 279, 281–284, 286, 287, 289, 290] this was restricted to stage 1 AKI [289], or subgroups such as percutaneous coronary interventions [278, 279], or cardiac surgery with propofol-free anaesthesia [283]. The meta-analyses are limited by risk of bias, heterogeneity in definitions of AKI, low event rates and underestimation of influence of co-morbidities [283, 289]. Finally, a Cochrane review including studies on patients undergoing surgery could not show a benefit on renal outcomes [178] (ESM_2 Table S16).…”
Section: Remote Ischaemic Preconditioningmentioning
confidence: 99%
“…A recent review addressed other effects of RIPC, including its influence on acute kidney injury and renal impairment among patients undergoing elective AAA repair. One study that looked at protective renal effects as the primary outcome found that RIPC had no significant impact on kidney damage, when assessed by serum creatinine levels and urinary output, whereas another reported a significant reduction in peak serum creatinine levels.…”
Section: Discussionmentioning
confidence: 99%
“…Patients undergoing coronary bypass surgery with induced RIPC in an upper extremity had a total reduction in levels of troponin by 43 per cent when measured by area under the curve, reflecting reduced perioperative myocardial ischaemia. The effects of RIPC in vascular surgery have been described previously. One randomized study showed that RIPC of the lower extremities during elective aortic surgery reduced the myocardial infarction (MI) rate from 27 to 5 per cent, and demonstrated a significant reduction in renal damage.…”
Section: Introductionmentioning
confidence: 85%